A case of aseptic osteomyelitis with heel ulcer improved by steroid application - Idogawa, M; Takahashi, H; Soma, T; Mihara, M; Mizukoshi, T; Murakami, R; Sugaya, T; Makiguchi, Y; Imai, K (Nihon Rinshō Menʾeki Gakkai kaishi, 2000)
A 43-year-old male patient was admitted to our hospital because of left heel pain and fever. He had had swelling of the left ankle joint and pain 4 years prior to this, and 4 years later, he was admitted to another hospital when left heel ulcer and fever developed. The ulcer was diagnosed and treated as a diabetic ulcer because of hyperglycemia. In spite of good control of blood sugar, the ulcer became enlarged and the pain deteriorated, so he was transferred to orthopedics. Antibiotics produced no response, and culture from a specimen of the ulcer was negative. However, severe inflammatory response was seen in blood examination. MRI and scintigram of his left foot showed disseminated low intensity areas and accumulation in the tarsal bone area, so osteomyelitis was suspected. A biopsy of the ulcer showed infiltration of inflammatory cells into the dermis. We considered amputation of the left lower leg at first. However the biopsy result suggested an autoimmune mechanism, so prednisolone was administered. As a result, the ulcer and pain both diminished. This case was similar to pyoderma gangenosum, however this diagnosis cannot explain osteomyelitis or all its symptoms. We expect that there must be other case report with the same symptoms.